Tropolone-Bearing Sesquiterpenes from Juniperus chinensis: Structures, Photochemistry and Bioactivity - Park, Jae Sung; Ko, Keebeom; Kim, Seong-Hwan; Lee, Jae Kyun; Park, Jin-Soo; Park, Keunwan; Kim, Mi Ri; Kang, Kyungsu; Oh, Dong-Chan; Kim, Sun Yeou; Yumnam, Silvia; Kwon, Hak Cheol; et al. (AMER CHEMICAL SOC, 2021)
The tropolone-bearing sesquiterpenes juniperone A (1) and norjuniperone A (2) were isolated from the folk medicinal plant Juniperus chinensis, and their structures were determined by a combination of spectroscopic and crystallographic methods. Photojuniperones A1 (3) and A2 (4), bearing bicyclo[3,2,0]heptadienones derived from tropolone, were photochemically produced and structurally identified by spectroscopic methods. Predicted by the machine learning-based assay, 1 significantly inhibited the action of tyrosinase. The new compounds also inhibited lipid accumulation and enhanced the extracellular glycerol excretion.
Keywords: PAPER CHROMATOGRAPHY; PHOTOELECTROCYCLIZATION; PHOTOCYCLIZATION; CONFINEMENT; HINOKITIOL; INHIBITORS; INDUCTION